The Influence of Social Media X on the Political Perspectives of Civic Education Students at Pamulang University - Varischa, Vivit; Sugiyanto, Sugiyanto (Wiyatamandala, 2026)
The development of information technology has made social media an important part of everyday life, including in the political realm. This study aims to determine the influence of social media X on the political perspectives of students in the Pancasila and Citizenship Education (PPKn) Study Program at Pamulang University. The study uses a quantitative approach with a causal associative method. The population of this study was all students of the Regular PPKn Study Program A, with a sample of 81 respondents selected through a proportionate stratified random sampling technique. The data collection technique used a questionnaire analyzed with validity, reliability, normality, linearity, and simple linear regression tests using SPSS version 25. The results showed that the use of X had a significant and positive effect on students' political perspectives with a significance value of 0.000 <0.05 and a coefficient of determination (R²) of 0.678. This means that 67.8% of the variation in students' political perspectives can be explained by the use of social media X. Thus, Social Media X plays a role in shaping students' understanding, attitudes, and involvement in political issues.